2006
DOI: 10.1089/dna.2006.25.287
|View full text |Cite
|
Sign up to set email alerts
|

CYP17,SRD5A2,CYP1B1, andCYP2D6Gene Polymorphisms with Prostate Cancer Risk in North Indian Population

Abstract: To investigate the involvement of the CYP17, SRD5A2, CYP1B1, and CYP2D6 variants with prostate cancer, a case-control study of 100 patients and an equal number of age-matched control men was conducted. There appears to be a nonsignificant increase with risk of prostate cancer for individuals carrying one copy of the CYP17 A2 allele (OR, 1.80; 95% CI, 0.99-3.29, P=0.05). The risk was increased in individuals having two A2 alleles (OR; 2.81, 95% CI, 1.06-7.40, P=0.03). Compared with men having the VV genotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Several polymorphic sites within the CYP1B1 gene (rs2617266, rs2567206, rs2551188, rs10012, rs1056836, rs1056827 and rs1800440) have been studied, but the rs1056836 (4326C/G, Leu432Val or L432V) site has been reported most frequently, albeit inconsistently, associated with increased PCa risk. [9][10][11][12][13][14][15] Some researchers have investigated the relationship between the CYP1B1 4326C/G polymorphism and PCa aggressiveness, although the definitions of low and high aggressiveness are different among these research reports.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymorphic sites within the CYP1B1 gene (rs2617266, rs2567206, rs2551188, rs10012, rs1056836, rs1056827 and rs1800440) have been studied, but the rs1056836 (4326C/G, Leu432Val or L432V) site has been reported most frequently, albeit inconsistently, associated with increased PCa risk. [9][10][11][12][13][14][15] Some researchers have investigated the relationship between the CYP1B1 4326C/G polymorphism and PCa aggressiveness, although the definitions of low and high aggressiveness are different among these research reports.…”
Section: Introductionmentioning
confidence: 99%
“…The CYP17 c.-34T!C polymorphism has been examined extensively in breast cancer with earlier studies, suggesting an increased risk of disease from the C allele (16,17), whereas more recent studies and meta-analyses do not support this link (18,19). Evidence for a link between the CYP17 c.-34T!C polymorphism and cancers of the ovary (20), endometrium (21), and prostate (22,23) were similarly inconsistent and controversial. Landi et al (33) reported no association between the current COMT polymorphism and risk of sporadic colon cancer in a casecontrol study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Common genetic polymorphisms have been reported to influence endogenous hormone levels (14,15). Polymorphisms in the sex steroid synthesis and metabolism genes cytochrome P450 17A1 (CYP17) and catechol O-methyltransferase (COMT) have been studied extensively in relation to risk of breast cancer (16 -19), and to a lesser extent, cancers of the ovary (20), endometrium (21), and prostate (22,23).…”
mentioning
confidence: 99%
“…A few epidemiologic studies have determined a positive association between this polymorphism and the Gleason score/clinical stage and serum PSA levels (Sobti et al 2006(Sobti et al , 2008 but many more conclusions are negative (Haiman et al 2001;Stanford et al 2002;Madigan et al 2003;Mononem et al 2006;Okugi et al 2006;Hamada et al 2007;Wright et al 2010;Risio et al 2011;Souiden et al 2011;Sivonova et al 2012;Yamada et al 2013;Han et al 2015;Henríquez-Hernández et al 2015;Brureau et al 2016;Song et al 2016). Some of the studies suggest that the CYP17A1 gene is a risk factor for PCa in males of advanced age (Souiden et al 2011;Song et al 2016).…”
Section: Cyp17a1 Rs743572 Gene Polymorphismmentioning
confidence: 99%